Diverse families: Challenges and social acceptance - Liñán Cuello, Yuly Inés; Mendoza López, Deibis Yaneth; Mejía González, Loreley (Revista de Ciencias Sociales, 2025)
The family is a social institution that has evolved by adapting to diversity and reflecting historical, economic, cultural, geographic, and political changes. Taking these elements into account, this article examines the challenges faced by diverse families, which represent alternative models to the traditionally accepted forms of monogamous and heterosexual families. This is a qualitative study, applying the method of documentary exploration and based on the review of academic sources with recognized institutional prestige. Among the main findings, the study highlights a break with the traditional model of the nuclear, monogamous family, characteristic of the bourgeois family, which generates prejudice and barriers against other family forms, particularly same-sex parent families, who face strong discrimination and stigmatization despite demonstrating their ability to function and thrive socially. The study concludes that diversity is an undeniable reality within families, and therefore requires full recognition and acceptance, overcoming existing prejudices and ensuring inclusive and democratic civic participation.